Changes in the Response Properties of Inferior Colliculus Neurons Relating to Tinnitus - Berger, Joel I.; Coomber, Ben; Wells, Tobias T.; Wallace, Mark N.; Palmer, Alan R. (Frontiers in Neurology, 2014)
Tinnitus is often identified in animal models by using the gap prepulse inhibition of acoustic startle (GPIAS). Impaired gap detection following acoustic over-exposure (AOE) is thought to be caused by tinnitus ‘filling in’ the gap, thus reducing its salience. This presumably involves altered perception, and could conceivably be caused by changes at the level of the neocortex, i.e. cortical reorganization. Alternatively, reduced gap detection ability might reflect poorer temporal processing in the brainstem, caused by AOE; in which case, impaired gap detection would not be a reliable indicator of tinnitus. We tested the latter hypothesis by examining gap detection in inferior colliculus (IC) neurons following AOE. Seven of nine unilaterally noise-exposed guinea pigs exhibited behavioural evidence of tinnitus. In these tinnitus animals, neural gap detection thresholds in the IC significantly increased in response to broadband noise stimuli, but not to pure tones or narrowband noise. In addition, when IC neurons were sub-divided according to temporal response profile (onset vs. sustained firing patterns), we found a significant increase in the proportion of onset-type responses after AOE. Importantly, however, gap detection thresholds were still considerably shorter than gap durations commonly used in objective behavioural tests for tinnitus. These data indicate that the neural changes observed in the IC are insufficient to explain deficits in behavioural gap detection that are commonly attributed to tinnitus. The subtle changes in IC neuron response profiles following AOE warrant further investigation.